The role of the learning management system usage and impact of the changes to the social interaction anxiety: a tentative model - Mazlan, Azriaty; Bolong, Jusang (Medwell Journals, 2017)
Learning management system is a relatively new phenomenon and until very recently their use of university was limited. Now the lecturers and the students have been pushing to use this system so that, they have a better and improved in a learning situation. The learning management system is already changing the organization and delivery of higher education. The pedagogical forces that have driven the higher learning institutions to adopt and incorporate ICTs in teaching and learning include greater information access and greater communication. The adoption of Technology Acceptance Model (TAM) which has two dimensions where Perceived Ease of Use (PEOU) is "the degree to which an individual believes that using a particular system would be free of physical and mental effort and Perceive Usefulness (PU) is defined as "he degree to which an individual believes that using a particular system would enhance his or her job performance. This concept study observes the impact of perceived ease of use, perceived usefulness on the extent of learning management system usage among university students. It is also looking at the moderating effect of learning management system usage between perceived ease of use, perceived usefulness and social interaction Anxiety. This research becomes a concern because a significant relationship social interaction anxiety was found between the level of problematic Internet use and social interaction anxiety. This study also observes the Anxiety/Uncertainty Management (AUM) Theory. In assessing social interaction anxiety among the predictors that can be counted on are perceived ease of use and perceived usefulness. Therefore, this study will elaborate some of the theory that is used in the previous study and some for the future study purposes.